Elimination of Lymphatic Filariasis: Mass Drug Administration in Endemic Areas of (Bidar District) Karnataka-2008 - T S Ranganath; N Ramakrishna Reddy (Indian Journal of Community Medicine, 2012)
Background : Lymphatic Filariasis is a mosquito transmitted disease, caused by parasitic worm Wuchereria bancrofti. Global Programme for Elimination of Lymphatic Filariasis was established in early 2000. The strategy recommended by the World Health Organization is annual Mass Drug Administration (MDA) of single-dose of Diethylcarbamazine 6 mg/kg (DEC), distributed to inhabitants of Filariasis endemic areas, excluding children below 2 years of age, pregnant women, and seriously ill persons, and Morbidity Management. The health system distributes the drugs by a door-to-door strategy. Objective : To assess the coverage and compliance of MDA in Bidar district during the campaign in November 2008. Materials and Methods: Cross-sectional population-based house-to-house visit. Outcome is assessed as actual coverage and compliance, in Percentage and proportions. Results: Eight clusters, total eligible population of 1 131 individuals were interviewed. The coverage rate was 78% with variation across different areas. The compliance with drug ingestion was 68%. Conclusion : The effective coverage was below the target (85%). Side effects of DEC were minimum, the overall coverage was better in rural areas compared with urban areas.